METHODS OF EVALUATING THE ECONOMIC EFFICIENCY OF INVESTMENT PROJECTS - Omonov Bahodir Fayzullo o‘g‘li (Scholar Express Journals, 2023)
This article describes the importance of investment policy in the development of the country's economy, the methods of assessing the economic efficiency of investment projects, analyzing the trends in the implementation of new investment projects and the support policy. Also, ways of further development of investment activities have been developed.
Keywords: investment; investment projects; efficiency; value